Avaliação nutricional de silagens de milho normal e com perfil de aminoácidos modificados - Helvecio Teixeira Vaz Oliveira (2006)
The nutritional value of three maizes hybrids silages (AG1051, 97HT131, and 97HT129), being the two last ones classified as Quality Protein Maize (QPM), was evaluated in assay carried out in the dependences of the Embrapa Gado de Leite, in Colonel Pacheco-MG, and Laboratory of Animal Nutrition of the School of Veterinary Medicine, in Belo Horizonte-MG, between July and August, 2003. It was evaluates the chemical composition, the dry and organic matter in vitro digestibility, in situ dry matter degradability, ruminal fermentation pattern, voluntary intake and milk and its components production. 21 cows (1/2 up to 7/8 Holstein/Zebu), from first until the fourth lactations, between 50 and 90 days of lactation, divided in random block design, and three rumen fistulated cows, in double Latin square, were used. Differences in the values of chemical composition, dry and organic matter in vitro digestibility, in situ dry matter degradability, ruminal fermentation patterns, voluntary intake and milk and its constituents production of the three silages had not been verified. It can be concluded that didnt have advantage in use of silages of QPMs maize hybrids in relation to the conventional hybrid for feed milk cows in lactation.